Analisis Model Dispersi Emisi Udara (SO2, NO2, dan TSP) Menggunakan Model Dari Software AERMOD Dengan Sumber Emisi Point Source - Raden Kokoh Haryo Putro; M. Ardiansyah Dwi Tama (Prosiding ESEC, 2023)
Production activities in the palm cooking oil and margarine industry generate emissions, both from combustion and non-combustion processes. This analysis aims to determine the results of the emission dispersion model from immovable sources on ambient air quality using AERMOD Software in the area around the Industry. The AERMOD modeling method is carried out by using generated emission load data, topography and meteorological data of activity locations for the last 10 years with air pollutant parameters measured including Particulates (TSP), Sulfur Dioxide (SO2) and Nitrogen Dioxide (NO2). After running the data, the results of the air emission dispersion modeling show that the highest concentration of emissions is located in settlements that are to the southeast of industrial emission sources. With the concentration of each parameter, namely for SO2 it is at 3.65 mg/Nm3 at a distance of 537 meters from the emission source, the NO2 parameter is at 5.98 mg/Nm3 at a distance of 497 meters, and the particulate parameter is at 1.31 mg/Nm3 with a distance of 498 meters. Distance can affect the emission concentration, namely the farther the distance from the emission source, the lower the emission concentration. Modeling using AERMOD shows that the dispersion of emissions on ambient air quality around the palm oil industrial area still meets the quality standards which refer to Government Regulation Number 22 of 2021 Appendix VII concerning Ambient Air Quality Standards.